2009
DOI: 10.1093/esr/jcp034
|View full text |Cite
|
Sign up to set email alerts
|

Stratification and Mortality--A Comparison of Education, Class, Status, and Income

Abstract: status -all can be used to show a "social gradient" with mortality, each of them seems to have a specific effect in addition to the general effect related to the stratification of society for either men or women.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
97
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(112 citation statements)
references
References 38 publications
11
97
0
4
Order By: Relevance
“…A causal link between education and health could, for instance, be the result of health literacy learned at school, such as the ability to make use of health messages (5). Alternatively, the link could be an indirect consequence of having a better job and a higher income (i.e., other circumstances related to good health) (6).…”
Section: Epidemiology | Natural Experimentsmentioning
confidence: 99%
“…A causal link between education and health could, for instance, be the result of health literacy learned at school, such as the ability to make use of health messages (5). Alternatively, the link could be an indirect consequence of having a better job and a higher income (i.e., other circumstances related to good health) (6).…”
Section: Epidemiology | Natural Experimentsmentioning
confidence: 99%
“…While existing comparative research on health inequalities has so far focused on objective SES indicators, such as education (Mackenbach et al, 2008), income (Huijts et al, 2010), or class (Eikemo et al, 2008b), our study will extend that line of research by focusing on an innovative SES measure, namely subjective SES. Different indicators of SES cannot be used interchangeably (Torssander and Erikson, 2010), as they all tap at different, loosely related aspects of SES and vary in the strength of their association to health. Given the variation in levels of subjective SES across countries (Lindemann and Saar, 2014), we expect that comparing subjective SES-health gradients across societies is a valuable contribution to the literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, research on factors other than demographics suggests that socioeconomic conditions may have a profound effect on risk of mortality, both in the general population and after SCI. [3][4][5] This research has typically focused on education and income to the exclusion of gainful employment as a risk factor for mortality.…”
Section: Introductionmentioning
confidence: 99%
“…9 These studies demonstrated the importance of income and education but did not address gainful employment. Studies in the general population have rarely addressed employment, [3][4][5] as employment is fundamental to adult life and employment rates are typically high. However, given the low employment rates and the relationship of poor employment outcomes with policy factors (particularly work disincentives in the USA), employment may be a critical, yet overlooked, risk factor for mortality.…”
Section: Introductionmentioning
confidence: 99%